1987
DOI: 10.1139/v87-128
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites produced by the Scleroderris canker fungus, Gremmeniellaabietina. Part 3. Some further metabolites

Abstract: WILLIAM A . AYER and M. SOLEDADE PEDRAS. Can. J. Chem. 65, 754 (1987).This article describes the metabolites of a strain of Gremmeniella abietina (Lagerb.) Morelet indigenous to Alberta. This strain does not produce the phenalenone derived metabolites isolated from the other strains of G. abietina examined to date. Only fatty acids and esters, glycerides, and sterol esters were produced. This raises a question regarding the identity of this particular strain. A greenish-yellow metabolite named Scleroderris gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For instance the intense but highly polar and extremely unstable dark violet pigments of Cortinarius violaceus turned out to be conjugates of ferric ions with beta dopamine, following several decades of intensive work aimed at their identification (von Nussbaum et al 1998), and many other pigments of these organisms still havel not been identified. The few true blue fungal pigments known to science include scleroderris blue from Gremmeniella abietina (Ayer et al 1986, Ayer and Pedras 1987), asperopterin A from Aspergillus oryzae (Kaneko and Sanada 1969) and 1-(3,8-Dimethyl-azulen-5-yl)-ethanone from sporocarps of Entoloma hochstetteri (Gill 1999). Several additional species of Entoloma also feature blue, and their pigments are likely azulene terpenoids as well.…”
Section: Discussionmentioning
confidence: 99%
“…For instance the intense but highly polar and extremely unstable dark violet pigments of Cortinarius violaceus turned out to be conjugates of ferric ions with beta dopamine, following several decades of intensive work aimed at their identification (von Nussbaum et al 1998), and many other pigments of these organisms still havel not been identified. The few true blue fungal pigments known to science include scleroderris blue from Gremmeniella abietina (Ayer et al 1986, Ayer and Pedras 1987), asperopterin A from Aspergillus oryzae (Kaneko and Sanada 1969) and 1-(3,8-Dimethyl-azulen-5-yl)-ethanone from sporocarps of Entoloma hochstetteri (Gill 1999). Several additional species of Entoloma also feature blue, and their pigments are likely azulene terpenoids as well.…”
Section: Discussionmentioning
confidence: 99%
“…53 A green pigment; scleroderris green (53) has also been reported from the culture of G. abietina. 53,82 This compound has a secondary amine function between two phenalenone moieties. Another compound; scleroderris yellow (54) was isolated from cultures of G. cassandrae, 53 having a methylene moiety between two monomers.…”
Section: Homodimers Of Phenalenonesmentioning
confidence: 99%
“…The uv-visible spectrum (A, , , 217,287, 305, 574 nm) and the color are similar to those of trypethelone (6). The 'H nmr spectrum of scleroquinone is like that of trypethelone (6) except that there is only one aromatic hydrogen (6 6.96, s) and there is a methoxyl signal (6 3.85). The presence of the ester functionality is indicated by ir absorption at 1740 cm-I, not present in trypethelone.…”
Section: Introductionmentioning
confidence: 71%
“…Further separation of fraction 1 by acid-base extraction gave a mixture that contained mainly phenolic compounds. Chromatography of this mixture (silica gel) using gradient elution (Skellysolve B-CHC13-CH30H containing HOAc) led to the isolation of sclerodin (I), scleroderolide (2), trypethelone (6), and small quantities of unidentified pigments. Further separation of fraction 2 by column chromatography (eluant: CHC13 -ethyl acetate -HOAc, 98:l:l) and preparative thin-layer chromatography led to the isolation of compounds 1 , 2, Sclerodems yellow (8), Sclerodems blue (3), and two unidentified red pigments.…”
Section: Separation Of Metabolites Of Sirococcus "336"mentioning
confidence: 99%